The Influence of Salt Solution on Morphological Changes in a Geosynthetic Clay Liner - Mochamad Arief Budihardjo (Advances in Materials Science and Engineering)
Morphological variations of geosynthetic clay liner (GCL) samples, hydrated with two different permeates, distilled water and NaCl solution (100 mM concentration), were observed in detail using microscopic analysis. After the GCL samples were hydrated with the NaCl solution, they were observed with an optical microscope. While the surface of the treated GCL samples was similar to the surface of the untreated GCL, a crystal deposit was found on the surface of the treated samples. Using a scanning electron microscope (SEM), a more solid appearance was observed for the bentonite particles contained in the GCL after the sample was hydrated with distilled water in comparison to the GCL sample that was hydrated with the NaCl solution. It appears that salt solution hydration results in less swelling of the bentonite particles. Furthermore, the energy-dispersive X-ray spectrometer (EDS) results showed that distilled water hydration had no effect on the distribution of the elements contained in the GCL samples. However, bound chlorine was observed, which demonstrated that the bentonite particles had absorbed the NaCl solution. In addition, changes in the hydraulic conductivity of the hydrated GCL samples were also observed.